Thermoregulatory Requirements Shape Mating Opportunities of Male Proboscis Bats - Wilde, Luke R.; Günther, Linus; Mayer, Frieder; Knörnschild, Mirjam; Nagy, Martina (Frontiers in Ecology and Evolution, 2018)
The spatiotemporal distribution of females is a major factor affecting animal social systems. Predation risk and the distribution of feeding resources often determine where females are found, but abiotic factors (e.g. temperature) can also shape the distribution of females and therefore variation in social organization and mating systems. Given the predicted future changes in climatic variation, it is vital to understand how animal mating systems and the sexual selection process may be altered by temperature. In bats, female distribution is tightly linked to roosting ecology and particularly to the microclimatic conditions at the roost. Proboscis bats (Rhynchonycteris naso) form cohesive and stable multi-male-multi-female groups and inhabit exposed day roosts (e.g. tree trunks, vines, buildings). Strong selection to remain inconspicuous to visually oriented predators in the exposed day roosts has been suggested to promote a rather rare male mating strategy termed site-specific dominance where males defend females directly but are successful in doing so only in their own territory. The choice of open-roost structures can result in the bats roosting under direct sunlight, making individuals susceptible to overheating. Here we investigate whether regular relocations of R. naso social groups among male territories are a mechanism of behavioral thermoregulation. Our results suggest that in general R. naso choose the warmest suitable roost sites within a roost, possibly to minimize the energetic costs of thermoregulation. However, on days with high midday temperatures at the primary roost site, bats commonly relocate to alternative, cooler sites within their roosts. These thermoregulatory relocations entail that a social group regularly switches among the territories of several males. Thus, the need for behavioral thermoregulation determines the spatial distribution of females and shapes the mating opportunities of males during the day. This is supported by our result that territorial males defending primary roost sites are reproductively more successful than territorial males of alternate roost sites. In line with other studies, our findings suggest that the increase in ambient temperatures associated with climate change has the potential to affect the intensity of sexual selection in bat species and may have far-reaching behavioral, demographic and evolutionary consequences for their populations.